Pollution Risk Assessment of Heavy Metals along Kitchener Drain Sediment, Nile Delta - Yasser A. El-Amier; Giuliano Bonanomi; Ahmed M. Abd-ElGawad (Soil Systems, 2023)
Population expansion within agricultural lands applies pressure on natural resources, particularly water resources, and leads to contamination through different types of pollutants, such as heavy metals, that consequently alter the ecosystem and impact human health. In the present work, several heavy metals in sediment along the Kitchener drain were assessed using different soil quality and health indices; the Kitchener drain is one of the major drains in the Nile Delta. Sediments were collected from six stations along the drain from upstream to downstream. Soil physical and chemical properties were analyzed as well as four metal pollution indices and five ecological risk indices. Additionally, carcinogenic and noncarcinogenic risks for adults and children were evaluated. The data showed that the Kitchener drain is mainly contaminated with Cd, Pb, and Zn, where the concentrations decreased from upstream to downstream. The eco-toxicological indexes showed that Pb, Zn, and Cr were the most hazardous metals along the drain, mainly at upstream stations. The human health risk indices data revealed that the noncarcinogenic risk of the studied metals can be ordered as follows: Co > Cr > Pb > Mn > Ni > Cd > Cu > Zn for adults, while for children it was Cr > Mn > Co > Pb > Ni > Cd > Cu > Zn. The carcinogenic risk data showed that heavy metals ranged from low to medium in all sites, except for Pb and Zn, which have high carcinogenic risks. The present study showed more contamination upstream compared to downstream which can be attributed to urbanization and human activity, as shown from the land use/landcover map. This highlighted that the major drains inside the Nile Delta suffer from different anthropogenic activities that should be taken into consideration by researchers, scientists, and policymakers. Also, the source of heavy metal pollution, particularly upstream, should be controlled or treated before discharge into the drain. On the other side, downstream (toward the Mediterranean Sea), the heavy metals could affect the trophic levels of the marine ecosystem on the Mediterranean Sea which should be taken into consideration.